The role of consumer leverage in generating financial crises - Dimova, D (University of Oxford, 2012)
Consumer leverage can generate financial crises characterized by increased bankruptcy, tightened credit access and reduced demand for goods. This paper embeds financial frictions in the mortgage contracts of homeowners within a two-sector economy to show that even at moderate initial levels, household indebtedness can create a lasting financial downturn such as the subprime mortgage crisis. Using two seemingly positive disturbances that triggered the subprime mortgage crisis - an increased housing supply and a relaxation of borrowing conditions - the model demonstrated that the subprime downturn was not a precedent but the natural consequence of financial frictions. The oversupply of houses lowers asset prices and reduces the value of the real estate collateral used in the mortgage. This worsens the leverage of indebted consumers and raised their bankruptcy prospects generating a pro-cyclical risk premium. A relaxation of borrowing conditions turns credit-constrained households into a potential source of disturbances themselves when market optimism allows them to overleverage with little downpayment. In both cases, the resulting excessive consumer leverage impairs household credit access for a lengthy after-shock period and diverts resources from their consumption. Their reduced demand for goods may propagate the downturn to the rest of the economy depressing output in other sectors. Adding credit constraints in the financial sector that provides housing mortgages deepens the negative impact of the shocks and makes recovery even more protracted.